Co-delivery of hydrophilic and hydrophobic anticancer drugs using biocompatible pH-sensitive lipid-based nano-carriers for multidrug-resistant cancers. Issue 48 (9th June 2017) - Naderinezhad, Samira; Amoabediny, Ghasem; Haghiralsadat, Fateme
Abstract : Simultaneous prolonged delivery of therapeutic gene, hydrophilic and hydrophobic anticancer drugs using biocompatible pH-sensitive LipoNiosome has been considered as a novel and promising method in order to treatment multi-drug resistant cancer. Abstract : For decades, multi-drug resistance (MDR) to chemotherapeutic drugs has been a serious challenge for researchers and has limited the use of anticancer drugs in malignancy treatment. Combination therapy has been considered as one of the most promising methods to address this problem. In the current study, we optimized niosome nanoparticles containing chemotherapeutic agent doxorubicin and chemosensitizer curcumin in term of surfactant content. Then, a new biocompatible structure (LipoNiosome, combination of niosome and liposome) containing Tween 60: cholesterol: DPPC (at 55 : 30 : 15 : 3) with 3% DSPE-mPEG was designed and developed to serve as a model for selective co-delivery of hydrophilic and hydrophobic drugs to cancerous cells. The proposed formulation provided potential benefits, including pH-sensitive sustained release, smooth globular surface morphology, high entrapment efficiency (∼80% for both therapeutic agents) and small diameter (42 nm). Exposure of cancer cells to LipoNiosome-doxorubicin–curcumin has shown an excellent performance of specific cellular internalization and synergistic toxic effect (>40%; as compared to free drugs and >23% when compared to single doxorubicin delivery) against Saos-2, MG-63 and KG-1 cell lines. A new cationic formulation (zeta potential: +35.26 mV; diameter: 52.2 nm) was also designed for co-delivery of above-mentioned drugs and gene as well. Finely, we suggested a kinetic model (Korsmeyer–Peppa with R 2 = 93% near cancer cells) for in vitro drug release of the co-delivery system. The presently formulated nano-based systems would provide researchers with a more obvious understanding of new LipoNiosome formulation as a successful lipid-based nano-carriers for co-delivery of doxorubicin, curcumin and other anticancer agents.